2011
DOI: 10.1007/s10484-011-9148-z
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Respiratory Rate Biofeedback Device to Reduce Dental Anxiety: An Exploratory Investigation

Abstract: Anxiety experienced by individuals visiting the dental office to receive treatment is common. Evidence has shown biofeedback to be a useful modality of treatment for numerous maladies associated with anxiety. The purpose of the current pilot study was to investigate the use of a novel biofeedback device (RESPeRATE™) to reduce patients' pre-operative general anxiety levels and consequently reduce the pain associated with dental injections. Eighty-one subjects participated in this study, forty in the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Additionally, continued studies on HF HRV biofeedback are warranted especially ones that specifically use PTSD measures as outcomes and incorporate at least eight training sessions. While no PTSD studies specifically focused on respiratory biofeedback have been conducted, slowed respiration rate training may help people with PTSD increase their HF HRV (Ginsberg et al 2010; Tan et al 2011; Zucker et al 2009) and reduce anxiety in general (Clark and Hirschman 1990; Morarend et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, continued studies on HF HRV biofeedback are warranted especially ones that specifically use PTSD measures as outcomes and incorporate at least eight training sessions. While no PTSD studies specifically focused on respiratory biofeedback have been conducted, slowed respiration rate training may help people with PTSD increase their HF HRV (Ginsberg et al 2010; Tan et al 2011; Zucker et al 2009) and reduce anxiety in general (Clark and Hirschman 1990; Morarend et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Physiological monitoring of breathing via a heart rate monitor or some other biofeedback device might be useful for both the patient and dental practitioner, 25 and has demonstrated effectiveness in reducing dental anxiety and negative feelings regarding a dental injection. 101 …”
Section: Diaphragmatic or Relaxation Breathingmentioning
confidence: 99%
“…Eight studies (Morarend et al, 2011;Moraveji et al, 2012;Parnandi et al, 2013;Vidyarthi and Riecke, 2013;Harris et al, 2014;Bhandari et al, 2015;Wu et al, 2015) reported using RSP biofeedback for coping with stress. Respiratory biofeedback systems measure and present breathing-related information (i.e., depth and frequency) to help users learn specific breathing skills for relaxation and stress relief.…”
Section: Respiratory (Rsp) Biofeedback (8 Studies)mentioning
confidence: 99%